The Search for Biomarkers and Microbial Fossils in Antarctic Rock Microhabitats - Ascaso, Carmen; Wierzchos, Jacek (Geomicrobiology Journal, 2003)
12 pages, 3 figures. The survival of lithobiontic microbial communities in Antarctica’s extreme cold, dry environment is conditioned by changes in external climatic conditions that can lead to the death of these microorganisms. In the present study, granite samples from maritime Antarctica and sandstone from the Antarctic continental desert were collected with the aim of searching for biomarkers and microbial fossils at the microscopic level of observation. The results reveal the presence of inorganic biomarkers in the form of physicochemical bioweathering mineral patterns, and inorganic deposits such as calcium oxalates and silica. The presence of fossilised algae and other microorganisms within the sandstone rock was also confirmed. Identifying the internal cell structure within the fossilised cells is proposed as a new criterion for the biogenicity of biomorphs. Peer reviewed